Exhaust emissions and conversion efficiency of catalytic converter for an ethanol‐fueled spark ignition engine. (11th April 2019) - Kim, Jaesoo; Myung, Cha‐Lee; Lee, Kyung‐Hwan
Abstract: The effects of the air‐fuel (A/F) ratio and spark timing on exhaust emissions and thermal efficiency were analyzed under part load conditions using an ethanol‐fueled spark ignition (SI) engine. The conversion efficiency of exhaust emissions after the application of a three‐way catalyst (TWC) to a gasoline engine was also evaluated. The cycle‐resolved measurement of hydrocarbon (HC) and NOx emissions was attempted, to investigate phenomena in the exhaust port with a fast‐response exhaust gas analyzer, and this was compared under different operating conditions. The different HC emission trends for the relative A/F ratios, as measured by a conventional exhaust gas analyzer and by the fast response analyzer, are thought to be due to differences in measuring location and the oxidation reaction of HC in the exhaust system. To optimize the ethanol A/F ratio to improve the conversion efficiency of TWC, it is thought that a slightly richer or leaner A/F ratio than stoichiometry would be better depending on the operating conditions and the levels of HC, CO, and NOx emissions, because the conversion efficiency of HC and CO is better with a leaner A/F ratio and the conversion efficiency of NOx is increased with a richer A/F ratio. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd